Agricultura familiar e segurança alimentar: a importância da produção para o autoconsumo - Hirai, Wanda Griep (2008)
The present dissertation approaches the theme of food security in the family agricultural context, having as its basis a research performed in the municipalities of Pelotas, São Lourenço do Sul and Canguçu. The focus of the study is centered upon the issue of self-consumption, which involves a myriad of practices adopted by families to ensure the full or partial demand of their feeding needs, both for immediate consummation products (vegetable or animal source) and transformed, which is the case of those items of the so-called rural domestic industry (cheeses, sausages, preserves, etc.). The self-consumption practices present a cultural matrix among rural families, in spite of the symbolic value attributed to products generated within the very rural establishment, as compared to the ones which are acquired externally in usual commerce or from other production units.The field-work was performed within 30 family agricultural establishments whose main commercial activity lies on the milk, peach and/or tobacco production. The results show that in spite of the several transformations which have occurred through time, the cultivation practices for self-provision still remain among the researched establishments, though this does not assure that this production be quantitatively and qualitatively sufficient to supply all the family group necessities. The decreasing number of people who comprise the family nucleus, the high cost of income, the scarcity of labor, and the absence of an agricultural politics which ensures satisfactory prices to products, all were named as factors which give economic vulnerability to the families in this region. The effort to answer to the new material necessities forces families to increase the production of commercial cultivation, thus sacrificing the selfconsumption production. The more and more frequent presence of vans which sell 8 horticulture farming products is a clear evidence in the decline of the performance level of self-consumption for a large number of rural families. family agriculture, food security, self-consumption.